Muslim-Christian polemics across the Mediterranean: the splendid replies of Shihāb al-Dīn al-Qarāfī (d. 684/1285) - Sarrió Cucarella, Diego R. (History of Christian-Muslim relations, 2015)
Preliminary Material -- Introduction -- 1 A Scholarly Life in Defense of Islam -- 2 A Handbook for Polemics -- 3 Al-Qarāfī’s Reply to the Letter to a Muslim Friend -- 4 Apologia Pro Religione Islamica -- 5 Christianity and the Innovation of A Wretched God -- 6 The Prophet Foretold -- Conclusion: The Prospects of Christian-Muslim Theological Dialogue -- Appendix A: Al-Qarāfī’s Literary Production -- Appendix B: The Arguments from The Letter to a Muslim Friend -- Appendix C: The Corruption of Early Christianity -- Appendix D: Biblical Predictions -- Bibliography -- Biblical References -- Qurʾānic References -- General Index.